In Vivo Role for Actin-regulating Kinases in Endocytosis and Yeast Epsin Phosphorylation - Watson, Hadiya A. (The American Society for Cell Biology, 2001)
The yeast actin-regulating kinases Ark1p and Prk1p are signaling proteins localized to cortical actin patches, which may be sites of endocytosis. Interactions between the endocytic proteins Pan1p and End3p may be regulated by Prk1p-dependent threonine phosphorylation of Pan1p within the consensus sequence [L/I]xxQxTG. We identified two Prk1p phosphorylation sites within the Pan1p-binding protein Ent1p, a yeast epsin homologue, and demonstrate Prk1p-dependent phosphorylation of both threonines. Converting both threonines to either glutamate or alanine mimics constitutively phosphorylated or dephosphorylated Ent1p, respectively. Synthetic growth defects were observed in a pan1–20 ENT1(EE) double mutant, suggesting that Ent1p phosphorylation negatively regulates the formation/activity of a Pan1p–Ent1p complex. Interestingly, pan1–20 ent2Δ but not pan1–20 ent1Δ double mutants had improved growth and endocytosis over the pan1–20 mutant. We found that actin-regulating Ser/Thr kinase (ARK) mutants exhibit endocytic defects and that overexpressing either wild-type or alanine-substituted Ent1p partially suppressed phenotypes associated with loss of ARK kinases, including growth, endocytosis, and actin localization defects. Consistent with synthetic growth defects of pan1–20 ENT1(EE) cells, overexpressing glutamate-substituted Ent1p was deleterious to ARK mutants. Surprisingly, overexpressing the related Ent2p protein could not suppress ARK kinase mutant phenotypes. These results suggest that Ent1p and Ent2p are not completely redundant and may perform opposing functions in endocytosis. These data support the model that, as for clathrin-dependent recycling of synaptic vesicles, yeast endocytic protein phosphorylation inhibits endocytic functions.